Chemical composition of diaspores of the myrmecochorous plant Stemona tuberosa Lour. (February 2016) - Chen, Gao; Huang, Sheng-Zhuo; Chen, Si-Chong; Chen, Yu-Han; Liu, Xu; Sun, Wei-Bang
Abstract: Diaspores of myrmecochorous plants often include nutrient rich elaiosomes, which are known as appendages of seeds to attract ants for seed dispersion. The benefits of myrmecochory were investigated thoroughly in previous studies, such as, the diaspores may be carried to the ant nests where the elaiosomes are consumed and the seeds are discarded unharmed. However, it remained unclear whether the secondary dispersers could shape the traits of diaspores in myrmecochory. In this study, we analyzed the nutritional quality of seeds and their corresponding elaiosomes of the myrmecochorous plant Stemona tuberosa (Stemonaceae), whose diaspores are dispersed by ants and/or hornets. Our results show significant differences in the quantitative pattern of nutrients between seeds and elaiosomes, respectively. The elaiosomes of S. tuberosa contain significantly higher concentration of proteins, free fatty acids, free amino acids, soluble carbohydrates, and micronutrients than the seeds. The low mass ratio of seed/elaiosomes in S. tuberosa compared to other myrmecochorous species imply that seed dispersal by hornets might be discriminated from seed dispersal by ants. In conclusion, we suggest that hornets and ants obtain the essential nutrients from the elaiosomes of S. tuberosa and these rewards contribute to shape the hornet/ant-plant mutualism. Highlights: Nutritional quality of diaspores of Stemona tuberosa was analyzed. Significant differences of nutrients were revealed between seeds and elaiosomes. Seed dispersal by hornets might be discriminated from seed dispersal by ants. Elaiosomes contribute to shape the hornet/ant-plant mutualism.